2005
DOI: 10.1103/physrevd.72.085001
|View full text |Cite
|
Sign up to set email alerts
|

Iteration of planar amplitudes in maximally supersymmetric Yang-Mills theory at three loops and beyond

Abstract: We compute the leading-color (planar) three-loop four-point amplitude of N = 4 supersymmetric Yang-Mills theory in 4 − 2ǫ dimensions, as a Laurent expansion about ǫ = 0 including the finite terms. The amplitude was constructed previously via the unitarity method, in terms of two Feynman loop integrals, one of which has been evaluated already. Here we use the Mellin-Barnes integration technique to evaluate the Laurent expansion of the second integral. Strikingly, the amplitude is expressible, through the finite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

110
1,909
3
17

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 823 publications
(2,039 citation statements)
references
References 152 publications
(279 reference statements)
110
1,909
3
17
Order By: Relevance
“…It also has a dual string theory description [19,20] provided by the AdS/CFT correspondence. From the perspective of the on-shell amplitudes it is not clear at present which of these features (if any) are responsible for the iterative structure uncovered in [1]. This makes it particularly interesting to investigate the amplitudes in theories related to the N = 4 SYM but with lower degree of symmetry.…”
Section: Jhep02(2006)040mentioning
confidence: 99%
See 1 more Smart Citation
“…It also has a dual string theory description [19,20] provided by the AdS/CFT correspondence. From the perspective of the on-shell amplitudes it is not clear at present which of these features (if any) are responsible for the iterative structure uncovered in [1]. This makes it particularly interesting to investigate the amplitudes in theories related to the N = 4 SYM but with lower degree of symmetry.…”
Section: Jhep02(2006)040mentioning
confidence: 99%
“…The proposal made in [1] gives an exponentiated ansatz which predicts the finite part of n-point planar MHV amplitudes in the superconformal N = 4 Yang-Mills to all orders…”
Section: Introductionmentioning
confidence: 99%
“…At the level of amplitudes, a generalization of the work of [6] to multiparton configurations has been provided in [9], proving an earlier statement [10] on the structure of single poles in QCD amplitudes at two loops. This was in turn an important ingredient in the formulation of a striking conjecture on the all-order structure of multileg amplitudes in N = 4 supersymmetric Yang-Mills theory, for which strong evidence was provided in [11,12]. A two-loop analysis of the soft functions appearing in the exponentiation of multiparton amplitudes was very recently started along these lines in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Organizing the Feynman diagrams by decomposed momentum and helicity, instead of momentum and polarized spin, has shown to dramatically reduce their complexity. These MHV diagrams share an iterative structure for computing higher loops [8].…”
Section: ) Where We Have Definedmentioning
confidence: 99%
“…In [8] it was found that maximally helicity violating (MHV) planar amplitudes in N = 4 SYM have an iterative structure for all n-point amplitudes. These results were then transferred to the β-deformed theory in [7] by placing the deformation into the so-called star product.…”
Section: Introductionmentioning
confidence: 99%